Blood urea nitrogen to serum albumin ratio is associated with all-cause mortality in patients with AKI: a cohort study - Shi, Yue; Duan, Hangyu; Liu, Jing; Shi, Xiujie; Zhang, Yifan; Zhang, Qi; Zhao, Mingming; Zhang, Yu (Frontiers in Nutrition, 2024)
Background This study aims to investigate the relationship between blood urea nitrogen to serum albumin ratio (BAR) and all-cause mortality in patients with acute kidney injury (AKI) and evaluate the effect of BAR on the prognosis of AKI. Methods Adult patients with AKI admitted to the ICU in the Medical Information Mart for Intensive Care IV (MIMIC-IV) were selected in a retrospective cohort study. BAR (mg/g) was calculated using initial blood urea nitrogen (mg/dl)/serum albumin (g/dl). According to the BAR, these patients were divided into quartiles (Q1–Q4). Kaplan–Meier analysis was used to compare the mortality of the above four groups. Multivariate Cox regression analysis was used to evaluate the association between BAR and 28-day mortality and 365-day mortality. The receiver operating characteristic (ROC) curve was plotted and the area under the curve (AUC) was calculated, and the subgroup analysis was finally stratified by relevant covariates. Results A total of 12,125 patients with AKI were included in this study. The 28-day and 365-day mortality rates were 23.89 and 39.07%, respectively. Kaplan–Meier analysis showed a significant increase in all-cause mortality in patients with high BAR (Log-rank p < 0.001). Multivariate Cox regression analysis showed that BAR was an independent risk factor for 28-day mortality (4.32 < BAR≤7.14: HR 1.12, 95% CI 0.97–1.30, p = 0.114; 7.14 < BAR≤13.03: HR 1.51, 95% CI 1.31–1.75, p < 0.001; BAR>13.03: HR 2.07, 95% CI 1.74–2.47, p < 0.001; Reference BAR≤4.32) and 365-day mortality (4.32 < BAR≤7.14: HR 1.22, 95% CI 1.09–1.36, p < 0.001; 7.14 < BAR≤13.03: HR 1.63, 95% CI 1.46–1.82, p < 0.001; BAR>13.03: HR 2.22, 95% CI 1.93–2.54, p < 0.001; Reference BAR ≤ 4.32) in patients with AKI. The AUC of BAR for predicting 28-day mortality and 365-day mortality was 0.649 and 0.662, respectively, which is better than that of blood urea nitrogen and sequential organ failure assessment. In addition, subgroup analysis showed a stable relationship between BAR and adverse outcomes in patients with AKI. Conclusion BAR is significantly associated with increased all-cause mortality in patients with AKI. This finding suggests that BAR may help identify people with AKI at high risk of mortality.